Coordination polymers of ZnII and 5-methoxy isophthalate. Issue 40 (23rd September 2015) - McCormick, Laura J.; Morris, Samuel A.; Teat, Simon J.; McPherson, Matthew J.; Slawin, Alexandra M. Z.; Morris, Russell E.
Abstract : Four different coordination polymers were prepared by reaction of Zn(OAc)2 and 5-methoxy isophthalic acid using various aqueous/aqueous alcohol solvent systems. Abstract : Solvothermal reaction of Zn(OAc)2 and 5-methoxy isophthalic acid (H2 MeOip) in aqueous alcohols ROH (R = H, Me, Et, or i Pr) affords four different novel coordination polymers. Zn2 (HMeOip)(MeOip)(OAc) (1 ) forms as a 1D 'ribbon of rings' polymer. Zn6 (MeOip)4.5 (HMeOip)(OH)2 (H2 O)2 ·5.5H2 O (2 ) crystallises as a complex 3D framework. Zn(MeOip)(H2 O)2 H2 O (3 ) is a 1D coordination polymer that contains almost planar strips of Zn(MeOip). compound4, Zn5 (MeOip)4 (OH)2 (H2 O)4 ·H2 O, obtained from aqueous i PrOH, crystallises as a 2D polymer containing two crystallographically distinct Zn5 (OH)2 clusters. Preliminary nitric oxide release experiments have been conducted.